Universities or “Professional” Schools: Where Are the Limits of the Academia-Industry Linkage (sangaku renkei) Policy? - Sýkora, Jan (Acta Orientalia Vilnensia, 2005)
Charles University, PragueWe touched this question for the first time about three years ago when we had started the tricky process of obtaining the official accreditation of our newly proposed curriculum in Japanese studies, which is the basic precondition for having right to provide education, to award degrees, and for gaining the financial support from the Ministry of Education, of course. The description of this process itself, which is mainly in hands of ministerial bureaucrats, would be, without any doubts, an excellent topic for another special lecture. However, I intend to focus on a particular problem concerning the perspectives on linkage between universities and industry / business only. The main goal of my brief paper is just to pose questions, summarize the main arguments, outline the pros and cons, and provoke the further discussion and inquiries rather than provide the definite answers to the mentioned question.